Effect of alley farming on weed infestation and floral composition - Akobundu, I.; Ekeleme, F.; Agyakwa, C.W. (1995)
Alley cropping with Leucaena leucocephala (Lam.) de Wit, caused a shift in weed flora away from fast-growing annual weeds that are characteristic of frequently cultivated fields to shade-tolerant, less-competitive weeds. Alley cropping caused a greater decline in weed density over lime than was observed in arable fields without alley cropping. This beneficial effect was reduced by the upsurge of shade-tolerant weeds and the build up of Leucaena volunteers where the Leucaena hedgerows were allowed to seed during a fallow period. Weed suppression was greater in Leucaena plots that were cropped every other year than in continuously cropped plots. One weeding within three weeks after planting maize was enough to minimize weed-related yield loss in the Leucaena alley cropping system, while plots without Leucaena hedgerows required twice as much weeding to minimize yield loss in maize by weeds.